Pengaruh Penerapan Teori Van Hiele Berbantuan Software Wingeom Terhadap Kemampuan Penalaran Matematika Siswa pada Materi Geometri - Fitri Amalia Izzati; Hadi Kusmanto; Toheri Toheri (ITEJ (Information Technology Engineering Journals), 2017)
One of the purpose of mathematics is to develop students’ mathematical reasoning abilities. But in the fact indicate that objective can’t be realized optimally. This research aims to determine the effect of application Van Hiele theory aided software wingeom to mathematical reasoning ability students on geometry. This research is case study with a sample of 40 students and using technique purposive sampling. The technique of collecting data used questionnaire and essay tests. Based on analysis of questionnaire obtained an average percentage of 63,04%, that means the student responded strongly. While mathematical reasoning ability is quite an average of 67,25%. Based on the hypothesis test analysis whit significance 5% show there is the effect of application Van Hiele theory aided software wingeom to mathematical reasoning ability on geometry. From the regression equation obtained = 8,482 + 0,847 X. The coefficient is positive, that means there is a positive correlation between the application Van Hiele theory aided software Wingeom and mathematical reasoning ability. The coefficient of determination 0,166 meaning that 16% variable mathematical reasoning ability is determined by the Van Hiele theory aided application software wingeom, while the remaining 84% is explained by other variable. The application of Van Hiele theory aided Wingeom software significantly affect students’ mathematical reasoning ability on geometry.